2022
DOI: 10.1039/d2py00489e
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly engineered dual-crosslinked elastomer vitrimers with superior strength, improved creep resistance, and retained malleability

Abstract: It’s very challenging to fabricate elastomer vitrimers that are both robust and dimensionally stable in service. Toward this issue, we initiate a multi-phase design of elastomer vitrimers by incorporating quadruple...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Compared with eSBR-HA 0.2 , new characteristic peaks appeared at 3307 and 1667 cm −1 in the spectra of ACM-modified SBR vitrimers, which was attributed to the stretching vibrations of N−H and C�O in amide groups, respectively (Figure 3a). 28,42 The signal intensity at 1667 cm −1 was significantly enhanced with the increasing ACM content. The formation of hydrogen bonding was further confirmed by variable temperature FT-IR.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Compared with eSBR-HA 0.2 , new characteristic peaks appeared at 3307 and 1667 cm −1 in the spectra of ACM-modified SBR vitrimers, which was attributed to the stretching vibrations of N−H and C�O in amide groups, respectively (Figure 3a). 28,42 The signal intensity at 1667 cm −1 was significantly enhanced with the increasing ACM content. The formation of hydrogen bonding was further confirmed by variable temperature FT-IR.…”
Section: Resultsmentioning
confidence: 95%
“…The strengthening and toughening mechanism of hydrogen bonding is described in Figure . During stretching, hydrogen bonds can dissipate large amounts of energy and diminish the stress concentration through prior rupture and reversible dissociation and reassociation, contributing an interesting combination of high strength and toughness. ,,, The physical cross-linking of hydrogen bonding can increase the modulus of elastomers. To further evaluate the energy dissipation during stretching, cyclic tensile experiments were performed (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12(A) ). 168 SAXS confirmed that only when the hydrogen bonding motifs were installed, phase separation was observed ( Fig. 12(B) ).…”
Section: Covalent Adaptable Network (Cans)mentioning
confidence: 72%
“…Phase separation induced by other hydrogen-bonding moieties are seen more often in CANs. 168,169 Some specific dynamic covalent groups are also known to form hydrogen bonds themselves. Dynamic covalent pyrazole-urea groups are, for example, known for their reversible BERs, but also for their potential to form intermolecular hydrogen bonds.…”
Section: Phase Separation In Cansmentioning
confidence: 99%